CUSTOMER SATISFACTION SURVEYS ON ORGANIZATION OF INDONESIAN FOOD AND DRUG AUTHORITY - Pitaloka, Endang; Avianti, Widiya (Jurnal Riset Bisnis dan Manajemen, 2023)
Indonesian Food And Drug Authority (BPOM) has the task of carrying out the preparation and implementation of policies, the preparation of norms, standards, procedures, criteria, the implementation of technical guidance and supervision. This study analyzes the Performance and Level of Service Importance (Importance Performance Analysis-IPA) in BPOM, in Quadrant I shows the highest service performance. In this quadrant there are indicators of Officer Cost and Behavior. On the cost indicator, it does not involve too many officers. Payment of services can be made by customers online with a virtual account. Customers assessing cost indicators are important aspects of the service and the assessment of its satisfactory performance "Good". This means that BPOM service products are in accordance with customer needs.